Pathogenic tau accelerates aging-associated activation of transposable elements in the mouse central nervous system. (January 2022) - Ramirez, Paulino; Zuniga, Gabrielle; Sun, Wenyan; Beckmann, Adrian; Ochoa, Elizabeth; DeVos, Sarah L.; Hyman, Bradley; Chiu, Gabriel; Roy, Ethan R.; Cao, Wei; Orr, Miranda; Buggia-Prevot, Virginie; et al.
Highlights: Retrotransposon transcripts increase in the aging brain and in three mouse models of tauopathy. Retrotransposon-encoded protein is elevated in brains of tau transgenic mice. DNA copy number of mobile retrotransposons is elevated in brains of tau transgenic mice. Abstract: Transposable elements comprise almost half of the mammalian genome. A growing body of evidence suggests that transposable element dysregulation accompanies brain aging and neurodegenerative disorders, and that transposable element activation is neurotoxic. Recent studies have identified links between pathogenic forms of tau, a protein that accumulates in Alzheimer's disease and related "tauopathies, " and transposable element-induced neurotoxicity. Starting with transcriptomic analyses, we find that age- and tau-induced transposable element activation occurs in the mouse brain. Among transposable elements that are activated at the RNA level in the context of brain aging and tauopathy, we find that the endogenous retrovirus (ERV) class of retrotransposons is particularly enriched. We show that protein encoded by Intracisternal A-particle, a highly active mouse ERV, is elevated in brains of tau transgenic mice. Using two complementary approaches, we find that brains of tau transgenic mice contain increased DNA copy number of transposable elements, raising the possibility that these elements actively retrotranspose in the context of tauopathy. Taken together, our study lays the groundwork for future mechanistic studies focused on transposable element regulation in the aging mouse brain and in mouse models of tauopathy and provides support for ongoing therapeutic efforts targeting transposable element activation in patients with Alzheimer's disease.